Cow Dung Is a Novel Feedstock for Fibrinolytic Enzyme Production from Newly Isolated Bacillus sp. IND7 and Its Application in In Vitro Clot Lysis - Vijayaraghavan, Ponnuswamy; Arun, Arumugaperumal; Vincent, Samuel Gnana Prakash; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah (Frontiers in Microbiology, 2016)
Bacterial fibrinolytic enzymes find great applications to treat and prevent cardiovascular diseases. The novel fibrinolytic enzymes from food grade organisms are useful for thrombolytic therapy. This study reports fibrinolytic enzyme production by Bacillus sp. IND7 in solid-state fermentation (SSF). In this study, cow dung was used as the cheap substrate for the production of fibrinolytic enzyme. Enzyme production was primarily improved by optimizing the nutrient and physical factors by one-variable-at-a-time approach. A statistical method (two-level full factorial design) was applied to investigate the significant variables. Of the different variables, pH, starch, and beef extract significantly influenced on the production of fibrinolytic enzyme (p < 0.05). The optimum levels of these significant factors were further investigated using response surface methodology. The optimum conditions for enhanced fibrinolytic enzyme production were 1.23% (w/w) starch and 0.3 % (w/w) beef extract with initial medium pH 9.0. Under the optimized conditions, cow dung substrate yielded 8,345 U/g substrate, and an overall 2.5-fold improvement in fibrinolytic enzyme production was achieved due to its optimization. This is the first report of fibrinolytic enzyme production using cow dung substrate from Bacillus sp. in SSF. The crude enzyme displayed potent activity on zymography and digested goat blood clot completely in in vitro condition.